Use of Video Analysis of Conflict Situations for Monitoring the Traffic on Urban Road Influenced by Parallel Parking - Vladislav Krivda; Ivana Mahdalova; Jan Petru (Communications - Scientific letters of the University of Zilina, 2013)
The paper deals with problems of influence of parallel parking on urban roads for road traffic safety. It shortly refers to evaluation of normative principles related to parking of road vehicles in the Czech Republic.It presents the results of analysis of traffic participant behavior on the particular section of inhabited area by use of video analysis of conflict situations. Thus it is pointed out to a possibility of application of this methodology in execution of safety inspections on roads, for example.